Caracterização da maturidade, compostos bioativos e qualidade sensorial de uvas apirênicas no vale do submédio São Francisco - Mascarenhas, Robson de Jesus (2009)
The objective of this research was to evaluate the physical, physical-chemical, bioactive, and sensorial attributes of the first Brazilian seedless grapes (Vitis vinifera L.) varieties 'BRS Clara', 'BRS Linda', 'BRS Morena', and Advanced Selection 8, compared with the North American 'Crimson Seedless'. Three experiments had been carried out. For the first one, taking into account the Normative Brazilian/2002 and the requirements for exportations, it was determined that Advanced Selection 8 develops large cluster, inserted in class 2, with dark reddish berry, caliber 20, and ellipsoid format; 'BRS Morena' presents cluster of medium size, in class 2, with berry colored of black nuance, caliber 20, and format between ellipsoid and globoid; 'BRS Linda' with large cluster, in class 2, light-green color, and 'Crimson Seedless' with pink colored and small cluster inserted in class 1, offer berries in caliber 18 with ellipsoid formats; 'BRS Clara' develops medium size cluster in class 2, berry with caliber, green yellowish green color and a format elongated ellipsoid. All of these grapes meet the standards for national market that demands a minimum of 12 millimeters of diameter. On the other hand, 'BRS Clara' does not meet the minimum diameter demanded for exportations. The red grapes ' BRS Morena' e 'Crimson Seedless' develop the firmest berries. The hydrogenionic potential, titratable acidity and soluble solids content meet the official standard values. The largest clusters are significantly less acid and present higher soluble solid/titratable acidity ratio, inferring to be the sweetest when mature. For the second experiment, it was determined and correlated the content of acid Lascorbic, total phenolic composites, trans-resveratrol, and the total antioxidative capacity of the studied grapes. All grape samples presented low acid L-ascorbic contents. The white 'BRS Clara' presents marked content of total phenolic compounds, followed by the white 'BRS Linda', in third position are the red ones: Advanced Selection 8, 'BRS Morena', and 'Crimson Seedless'. 5 Grapes presented distinct contents of trans-resveratrol in this following order of superiority: 'BRS Morena', 'Crimson', Advanced Selection 8, 'BRS Linda', and 'BRS Clara'. Trans-resveratrol seems to provide varietal identity. Red grapes presented higher contents of trans-resveratrol. 'BRS Clara', ' Crimson Seedless', and 'BRS Linda', similarly, presented the highest antioxidative capacity and the color of the grape did not influence on that. The contents of total extractable phenolic compounds influenced positively on the antioxidative capacity. Grapes presenting larger contents of total extractable phenolic compounds presented lower content of transresveratrol. For the third experiment it was used the Quantitative Descriptive Sensorial Analysis, by means of selected and trained judges. On the global quality, 'BRS Morena' was superior than others grapes evaluated, while Advanced Selection 8 was in second position, and 'BRS Linda' and 'Crimson Seedless' occupied the third position, while 'BRS Clara' showed the most inferior sensorial quality. The general characteristics flavor, with large superiority, followed, in this order, by the strongest tonality, the red color, the most spherical format, the highest firmness, succulence, crispness, and sweetness contributed positively with the global quality. The bitter taste and the sensorial acidity, in this sequence of intensity, were the attributes of larger negative influence. The results for physical and physical-chemical evaluations, together, reflect significantly the sensorial perceptions. Therefore, once inserted in the official standards of identity and quality, beside the varietal characteristic flavor, producers must prefer to produce grapes of stronger tone, larger sizes, and more spherical or globular formats.